E06 Temporo-spatial structural characterization of deep white matter tracts across the spectrum of Huntington's disease. (12th September 2022) - Domingo-Ayllon, Montserrat; Garcia-Gorro, Clara; Martinez-Horta, Saül; Perez-Perez, Jesus; Kulisevsky, Jaime; Rodriguez-Dechicha, Nadia; Vaquer, Irene; Subira, Susana; Calopa, Matilde; Muñoz, Esteban; Santacruz, Pilar; Ruiz-Idiago, Jesus; et al.
Abstract : Background: Although white matter (WM) abnormalities and subcortical iron accumulation are causal factors of neurodegeneration in Huntington's disease (HD), their specific role is not clear yet. Aims: To understand the dynamics of the physiopathology process underlying in HD by using a multimodal temporo-spatial characterization of WM tracts (microstructural integrity and iron content). Methods: Thirty-one HD gene-expansion carriers (12 premanifest, 19 manifest) and 24 healthy controls participated in this study. DTI and T2*-relaxometry were employed to characterize the structural connectivity and the iron distribution of eighteen main WM tracts. Three approaches have been used for the statistical analysis: average measure, segmental measures based on anatomic division of the tracts, and measures along the tract considering multiple points. Results: Striatal medium spiny neurons are the most affected entailing basal ganglia atrophy with disruption of cortico-basal ganglia-thalamocortical circuits. Consequently, different WM tracts included in these circuits are presumed to be affected in presymptomatic stages as demonstrated in our study: motor function depending on putamino-pallidal connections (CST), limbic system depending on ventral striatum (cingulate), and executive function depending on caudate (ATR, forceps minor and forceps major). Associative tracts (uncinate, inferior longitudinal, superior longitudinal fronto-parietal and fronto-temporal fasciculus) are also altered in symptomatic stages, most probably as a consequence of transaxonal degeneration when the brain breaks down globally. Conclusion: This study has allowed to depict the temporo-spatial dynamics of WM tracts disintegration in HD. In particular, while all tracts showed widespread disintegration as the disease progress, motor-related tracts present higher iron levels than non-motor-related tracts.